Avaliacao osteomuscular, cardiovascular e metabolica em mulheres com obesidade submetidos a cirurgia bariátrica - Carvalho, Nara Nóbrega Crispim (2023)
We evaluated musculoskeletal, cardiovascular and metabolic parameters in obese women with and without parameters related to sarcopenic obesity (SO), before and after the follow-up of bariatric surgery (BS). Secondarily, we compared these parameters between the two groups and evaluated the prospective association of low muscle mass or low muscle strength with bone mineral density (BMD). Participants were recruited in 2018 and the sample was evaluated and subsequently divided into two groups: individuals with SO parameters (SOP) and individuals without SO parameters (OB group). Parameters related to sarcopenia were defined as low handgrip strength (HG) and/or low appendicular skeletal mass adjusted for weight (ASM/weight × 100, %). Body composition (bioimpedance), BMD (dual-energy X-ray absorption), metabolic and inflammatory profiles, blood pressure (BP) and heart rate variability (HRV) were evaluated. The surgical techniques performed were Roux-en-Y gastric bypass (RYGB) or sleeve gastrectomy (SG).Weight loss was similar between groups (p>0.05). Both groups underwent gastric bypass and sleeve gastrectomy in the same proportion (p>0.05). Weight, body mass index (BMI), fat mass, body fat percentage (BFP), lean mass, fat-free mass (FFM), fat-free mass index, and HG were reduced in both groups during the first year followup (p<0.05). Women with SOP had lower FFM, ASM/weight × 100.% and HG than those with OB (p<0.05). Total cholesterol, LDL-cholesterol, triglycerides, fasting blood glucose, glycated hemoglobin, insulin and homeostatic model assessment-insulin resistance (HOMA-IR) were reduced, while HDL-cholesterol increased in both groups over one year (p<0.05). Both groups showed reduced BMD at all sites [lumbar spine (LS), femoral neck (FN) and total femur (TF)] over one year of follow-up (p<0.05). The SOP group had lower BMD, Z score and T score in LS and FN compared to the OB group (p<0.05). A positive prospective association was observed between LS and FN BMD with the MMEA/weight quartile, regardless of age, BMI, body fat and HOMA. Regarding the BP and HRV variables, there was a reduction in diastolic blood pressure, heart rate, SDHR (standard deviation of successive RR intervals), LF (normalized unit in the low frequency band) and LF/HF (p<0.05) and an increase of the HF band (normalized unit in the high frequency band) in both groups during the follow-up period (p<0.05). SOP group had a reduction in the square root mean square difference between adjacent normal RR intervals (RMSSD) and the HF band, and an increase in the LF band and SD2/SD1 ratio (SD2; Poincaré standard deviation plot perpendicular along the line of identification/SD1; Poincaré plot standard deviation perpendicular to the identification line) compared to the OB group over a one-year period (p<0.05). ASM/weight × 100, % was negatively associated with the LF band (p<0.05) and positively associated with the HF band (p<0.05). On the other hand, FPP had no significant association with LF and HF. ASM/weight × 100, % and HG were negatively associated with the LF/HF ratio (p<0.05). We conclude that women with SOP had greater loss of BMD and less pronounced improvement in HRV at the one-year follow-up after BS.